Experimental Evidence for the Existence of Other Mutually Invisible Universes Neighboring Our Visible Universe - Antonov, Alexander Alexandrovich (European Journal of Applied Sciences, 2024)
The article explains that the special theory of relativity (SRT), created in the early twentieth century, which is an outstanding scientific achievement, was ahead of its time, because science then lacked some of the knowledge necessary for its creation - not used discrete mathematics, was not explained the physical meaning of imaginary numbers, were not discovered dark matter and dark energy and in space has not yet launched spacecraft WMAP, Planck and others. Therefore absence of the mentioned knowledge was justifiably replaced by postulates. But not everything was guessed. And present now in the version of SRT studied in all physics textbooks, the postulate called the principle of non-exceeding the speed of light turned out to be incorrect. Therefore the corrected version of SRT in which this postulate is replaced by the experimentally proved principle of physical reality of imaginary numbers is offered. In this corrected version of SRT also offered a experimental proof of the existence of mutually invisible parallel universes astronomical observations in portals invisible outside the portals of constellations. And it is explained, why the principle of non-exceeding of speed of light not disproved so far by physical experiments is incorrect.